A Retrospective Study on the Use of Dermis Micrografts in Platelet-Rich Fibrin for the Resurfacing of Massive and Chronic Full-Thickness Burns - Alessandro Andreone; Daan den Hollander (Stem Cells International)
The coverage of massive burns still represents a big challenge, even if several strategies are to date available to deal with this situation. In this study, we describe the use of a combination of platelet-rich fibrin and micrograft spray-on skin in order to increase the yield of grafted cells in patients. We treated a total of five patients, of which two were affected by massive burns and three with chronic burn wounds. Briefly, autologous micrografts were obtained by Rigenera technology using a class I medical device called Rigeneracons. The micrografts were then combined with PRF and sprayed on the wound bed by a Spraypen. Before applying PRF/micrograft spray-on skin, the wound bed was covered with an Integra® dermal template, and the wounds were dressed with a layer of antimicrobial dressing applied directly over the silicone layer. When the silicone layer of the dermal template started showing signs of separation, the wound was considered ready for grafting. In all cases, we observed a fast and complete skin graft on average after 7-10 days by PRF/micrograft spray-on skin treatment. In particular, two patients with massive burns reported rapid reepithelialization, and three patients with chronic burn wounds, two of whom had failed skin grafts before the procedure, had complete wound healing within a week. In conclusion, the results showed in this study suggest that the use of PRF/micrograft spray-on skin represents a promising approach in the management of burns or chronic burn wounds.